PROFIL KEMISKINAN BURUH PETANI KARET DI DESA TERATAK DOMO KELURAHAN PASIR SIALANG KECAMATAN BANGKINANG SEBERANG KABUPATEN KAMPAR - Nike Faramyta; M Razif " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Poverty is one of the most serious social problems. However he define poverty in will show the bad side of life that awaits a solution. Poverty is the worst state for man in the life of a complex society. Most of the poor are in rural areas, rural community known as hard workers because hard work is an important requirement in order to survive, the geographical factor is very influential for villagers as tied to the land and their dwellings harness nature for survival.The purpose of this study to determine the poverty profile in rubber farmer workers. This study is a qualitative research data collection techniques used in research that is through in-depth interviews and observation to 8 respondents. The unit of analysis is the study of socio-economic and cultural conditions of laborers rubber farmers, laborers factors rubber farmers stick with the job. And poverty indicators used by Dalil Hasan. The results show how the poverty profile of workers rubber farmers. This study suggests that workers rubber farmers in the area of research should be more observant in the search for business opportunities in increasing revenue, because if the only hope of tapping rubber it will be difficult to achieve revenues in excess.Keywords: Poverty, Labor rubber farmers, Qualitative Analysis